A qualitative descriptive study on the meaning of suicide among college students - Darni Darni; M Akbar Nugraha; Ramdya Akbar Tukan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Suicide is a major public health issue, and the underlying causes have not been definitively identified. Suicide instances continue to be prevalent in media coverage, and there is a rise in the incidence of suicides. In 2023, the incidence of suicides among junior high school students was highest in Central Java with 253 cases, followed by East Kalimantan with 128 cases, and North Kalimantan with 4 cases. Purpose: To investigate the significance, understanding, origins, outcomes, and anticipations of students regarding suicide incidents in coastal regions. Method: This was a descriptive qualitative study. The participants in this study were students from coastal areas. The number of respondents was 13. Data collection using in-depth interviews with interview guidelines, field notes, and data collection results was analyzed using Collaizzi. Results: This study identified four themes: comprehension of suicide incidents in coastal border areas, and factors that lead individuals to commit suicide in coastal zones. Events occurring post-suicide and suicide events are absent in coastal villages. Conclusion: Suicide among students in coastal border regions is shaped by limited awareness, personal and familial stressors, and varied social reactions. While some responses to suicide attempts involve sympathy and support, others perpetuate stigma and exclusion, reinforcing negative narratives.